The Spectrum of Cyclopentanone - Howard-Lock, Helen Elaine (My University, 1968)
The infrared, Raman and ultraviolet spectra of cyclopentanone, cyclopentanone -α,α,α',α'-d₄ and cyclopentanone-d₈ have been studied. The high resolution ultraviolet absorption spectra of the three isotopic species have been analysed in detail. The electronic transition has been identified as a single-singlet transition associated with ṉ→π* orbital electron promotion. The vibrational and rotational structures accompanying this electronic transition have been analysed and the results are in agreement with theoretical predictions. The geometry of the molecule in both ground and excited states has been calculated. In the excited state conformation, the oxygen atom is bent out of the plane of the three adjacent carbon atoms; there is a potential barrier of 705cm⁻¹ with respect to the oxygen out-of-plane bending vibration in the upper state.
Keywords: chemical physics; infrared; Raman; ultraviolet; spectrum; cyclopentanone; cyclopentanone-α,α,α',α'-d₄; cyclopentanone-d₈